Human melanocytes mitigate keratinocyte-dependent contraction in an in vitro collagen contraction assay. Issue 5 (August 2015) - Rakar, Jonathan; Krammer, Markus P.; Kratz, Gunnar
Graphical abstract: Highlights: We used in vitro contraction assays to investigate keratinocytes, fibroblasts and melanocytes. We used human primary cells from multiple individuals, with patient-matched assays. Melanocytes mitigate keratinocyte-dependent contraction. Contact co-cultures show more prominent effects than non-contact co-cultures. Abstract: Scarring is an extensive problem in burn care, and treatment can be especially complicated in cases of hypertrophic scarring. Contraction is an important factor in scarring but the contribution of different cell types remains unclear. We have investigated the contractile behavior of keratinocytes, melanocytes and fibroblasts by using an in vitro collagen gel assay aimed at identifying a modulating role of melanocytes in keratinocyte-mediated contraction. Cells were seeded on a collagen type I gel substrate and the change in gel dimensions were measured over time. Hematoxylin & Eosin-staining and immunohistochemistry against pan-cytokeratin and microphthalmia-associated transcription factor showed that melanocytes integrated between keratinocytes and remained there throughout the experiments. Keratinocyte- and fibroblast-seeded gels contracted significantly over time, whereas melanocyte-seeded gels did not. Co-culture assays showed that melanocytes mitigate the keratinocyte-dependent contraction (significantly slower and 18–32% less). Fibroblasts augmented the contraction in most assays (approximately 6% more). Non-contact co-cultures showed some influence on the keratinocyte-dependent contraction. Results show that mechanisms attributable to melanocytes, but not fibroblasts, can mitigate keratinocyte contractile behavior. Contact-dependent mechanisms are stronger modulators than non-contact dependent mechanisms, but both modes carry significance to the contraction modulation of keratinocytes. Further investigations are required to determine the mechanisms involved and to determine the utility of melanocytes beyond hypopigmentation in improved clinical regimes of burn wounds and wound healing.